Is Coronavirus-19 Phobia of Sports Science Students a Barrier to Their Levels of Physical Activity in "Controlled Normalization"? A Cross-Sectional Study - Güler, Melek; Yanar, Nazlı (International Journal of Asian Education, 2022)
COVID-19, which affects the world, undoubtedly seems to have affected university students who receive applied education. Sports Science students continue their sports training within the mask and distance rules by switching to face-to-face teaching during the normalization period. This study aimed to reveal whether the physical activity levels of Sports Science students were affected by Coronavirus-19 phobia after switching to face-to-face training.  432 (female; 152, male; 280) university students from Sports Sciences attended the research. Data from the participants were collected using the Coronavirus-19 Phobia Scale and the International Physical Activity Questionnaire-Short Form (IPAQ-SF). The independent sample and Mann-Whitney U test, One-Way, and two-way ANOVA test (Post hoc Tukey) were used in the data analysis. According to the results, the 'psychological' sub-dimension scores of the participants, an increase in body mass index, not doing sports, reducing the vaccine dose, spending COVID-19 in the hospital, and wearing a mask in practical classes increase. In addition, those who wear masks in applied lessons have higher ‘somatic,’ ‘social,’ and ‘economic’ sub-dimension scores. Females' coronavirus-19 phobia, ‘psychological’ and ‘economic’ sub-dimensions, and total scale scores are higher than males. Consequently, with the increased physical activity levels of Sports Science students, coronavirus-19 decreases phobia scores